Visual search strategy during regatta starts in a sailing simulation - Manzanares, A.; Menayo, R.; Segado, F. (Motor control, 2017)
In a sport conditioned by natural elements such as sailing, visual perception is a key factor for the performance. Research has shown that the visual behavior of athletes at different skill levels varies, which may cause differences in the performance achieved. The aim of this research was to examine the visual behavior of sailors from different ranking positions at the start of a race in a simulated situation. Twenty junior sailors (N=10 top and N=10 bottom ranking) participated in this study. The visual behavior was recorded at the start of a sailing simulation. The top-ranking sailors performed more visual fixations on the locations that have more highly relevant information, such as "telltales" and "rivals"? than do bottom-ranking sailors (p<.005). The top-ranking sailors are closer to the start line at the time of the start signal. The analysis of the visual search strategy shows that top-ranking sailors employed a more active visual search strategy. More experienced athletes can make better use of the information obtained from the important locations.